Pengembangan Media Kartu Bergambar Kartun Serial Televisi Pada Materi Teks Prosedur Terhadap Peserta didik Kelas IV - Munajah, Robiatul; Nabila (LPPM Press, 2025)
Writing skills constitute a crucial aspect of developing literacy competence among elementary school students. However, preliminary observations indicate that most students still experience difficulties in constructing procedural texts in a coherent manner and in accordance with appropriate linguistic conventions. This study aims to develop Television Cartoon Series Picture Card media to enhance the procedural text writing skills of fourth-grade students at SDN Kebon Baru 07 Jakarta.This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data were collected through teacher interviews, classroom observations, documentation, and learning outcome tests. Data analysis techniques included quantitative descriptive analysis to assess the feasibility of the developed media based on expert validation percentages, as well as analysis of learning improvement using the N-Gain test. The results indicated that the developed media were highly feasible for use, as evidenced by expert validation scores of 98.57% from subject matter experts, 92.94% from media experts, and 90% from language experts. Effectiveness testing conducted on a small scale involving 15 students yielded an average N-Gain score of 0.49, categorized as moderate. Meanwhile, large-scale trials involving 26 students demonstrated a higher improvement, with an average N-Gain score of 0.77, categorized as high. These findings demonstrate that the Television Cartoon Series Picture Card media are effective in improving elementary school students’ understanding and writing skills in procedural texts.